Pengaruh Pengembangan Karir Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Kantor Desa Negara Ratu Kecamatan Natar Kabupaten Lampung Selatan - Chairani, Rifda; Nouval , Farid (LPPM STIE KRAKATAU, 2017)
The research conducted is explanatory research. This study uses 52 research respondents. Thereare three variables in this study are: two (2) independent variable (X1) and (X2) and 1 (one)dependent variable (Y) in which career development (X1) and work motivation (X2) as theindependent variable and the employees performance (Y) as the dependent variable. Based on theresults of data analysis answers the following hypothesis; there is the influence of careerdevelopment (X1) toward employee performance (Y) with the degree of influence (R-square) of33.9%. There is the influence of work motivation (X2) toward employee performance (Y), with thedegree of influence of 30.8%. There is the influence of career development (X1) and workmotivation (X2) by simultan toward employee performance (Y) with a degree of influence at 35.1%.